Evaluasi Pengupasan Volume Overburden Menggunakan Data Truck Count Monitoring dan Joint Survey di Pit Batu Tegak PT. Andalan Artha Primanusa Jobsite PT. Budi Gema Gempita, Merapi Timur, Kabupaten Lahat, Sumatera Selatan - Gilang Oktafi Hendri; Riko Maiyudi; Heri Prabowo; Rudi Anarta (Departemen Teknik Pertambangan FT UNP, 2023)
PT. Andalan Artha Primanusa Jobsite PT. Budi Gema Gempita is a coal mining company operating in East Merapi District, Lahat Regency, South Sumatra. The mining system uses an open pit mining system with the Open Pit Mining method. In carrying out mining operations, there is a deviation from the overburden production results from the data recorded by the checkers in the form of truck count monitoring data and measurement results data from surveys in the form of joint survey data. After calculating the overburden volume, the overburden volume deviation was obtained based on survey data and truck count monitoring data at the May 2022 EOM of 17,053.99 bcm with a percentage value of 4.52% and in June 2022 there was a deviation of 21,368.58 bcm with a percentage value of 6.58%. From these results it can be seen that the deviation value obtained exceeds the standard set by the company, namely with a percentage of ± 3%. Because the results of the deviation exceed the standard set, a picking test of the load of the conveyance is carried out. Based on the results of the picking test, there is a difference in the volume of the Joint Survey data with the Truck Count Monitoring data of 5,920.58 bcm with a percentage of 1.82%. This is due to the presence of sticky overburden material on the vessel dump truck or articulated dump truck and not dredging, so that the load on the vessel is not optimal. Meanwhile, by looking at the survey measurement conditions, there are areas that have not been measured because they are still submerged in water.